Linc01234 promotes cell proliferation and metastasis in oral squamous cell carcinoma via miR-433/PAK4 axis - Deyu Liu; Xinchun Jian; Pu Xu; Rong Zhu; Yuan Wang (BMC Cancer, 2020)
Abstract Background Increasing studies have demonstrated that long non-coding RNAs (lncRNAs) play an important role in tumor progression. However, the potential biological functions and clinical importance of Linc01234 in oral squamous cell carcinoma (OSCC) remain unclear. Methods We evaluated the expression profile and prognostic value of Linc01234 in OSCC tissues by RT-qPCR. Then, functional in vitro experiments were performed to investigate the effects of Linc01234 on tumor growth, migration and invasion in OSCC. Mechanistically, RT-qPCR, bioinformatic analysis and dual luciferase reporter assays were performed to identify a competitive endogenous RNA (ceRNA) mechanism involving Linc01234, miR-433-3p and PAK4. Results We found that Linc01234 was clearly upregulated in OSCC tissues and cell lines, and its level was positively associated with T stage, lymph node metastasis, differentiation and poor prognosis of patients with OSCC. Our results shown that Linc01234 inhibited cell proliferation and metastatic abilities in CAL27 and SCC25 cells following its knockdown. Mechanistic analysis indicated that Linc01234 may act as a ceRNA (competing endogenous RNA) of miR-433-3p to relieve the repressive effect of miR-433-3p on its target PAK4. Conclusions Our results indicated that Linc01234 promotes OSCC progression through the Linc01234/miR-433/PAK4 axis and might be a potential therapeutic target for OSCC.